2021
DOI: 10.3892/etm.2021.9612
|View full text |Cite
|
Sign up to set email alerts
|

FABP4 alleviates endoplasmic reticulum stress‑mediated ischemia‑reperfusion injury in PC12 cells via regulation of PPARγ

Abstract: Ischemic stroke is a life-threatening complication with a high rate of morbidity. Circulating fatty acid binding protein 4 (FABP4) has been reported to be associated with the outcome of acute ischemic stroke. The present study aimed to illustrate the function of FABP4 in ischemic stroke. PC12 cells exposed to oxygen glucose deprivation/reoxygenation (OGD/R) were used to mimic ischemia-reperfusion (I/R) injury in ischemic stroke. Cell viability was estimated using a Cell Counting Kit-8 assay. The expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…FABP4 is also involved in oxidative stress and inflammation. FABP4 reduces cyclooxygenase‐2 and inducible nitric oxide synthase expression in macrophages through IKK‐NF‐κB and JNK‐AP‐1 pathways, 15 and thus promotes oxidative stress response. FABP4 also regulates the expression of inflammatory cytokines, such as interleukin (IL)‐1β, IL‐6, and TNF‐α, and thus promotes inflammatory necrosis 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FABP4 is also involved in oxidative stress and inflammation. FABP4 reduces cyclooxygenase‐2 and inducible nitric oxide synthase expression in macrophages through IKK‐NF‐κB and JNK‐AP‐1 pathways, 15 and thus promotes oxidative stress response. FABP4 also regulates the expression of inflammatory cytokines, such as interleukin (IL)‐1β, IL‐6, and TNF‐α, and thus promotes inflammatory necrosis 15 .…”
Section: Discussionmentioning
confidence: 99%
“…FABP4 reduces cyclooxygenase‐2 and inducible nitric oxide synthase expression in macrophages through IKK‐NF‐κB and JNK‐AP‐1 pathways, 15 and thus promotes oxidative stress response. FABP4 also regulates the expression of inflammatory cytokines, such as interleukin (IL)‐1β, IL‐6, and TNF‐α, and thus promotes inflammatory necrosis 15 . FABP4 can also upregulate the expression of adhesion molecules, such as integrin β2, α4, P‐selectin ligand protein, intercellular cell adhesion molecule 1 (ICAM‐1), vascular cell adhesion molecule 1 (VCAM‐1), and P‐selectin, and thus promote ox‐LDL‐induced cell adhesions and AS development 11 …”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that FABP4 deficiency can inhibit IKK-NF-κB and JNK-AP-1 pathways, reducing the expression of cyclooxygenase-2 and inducible nitric oxide synthase in macrophages [ 28 ], which relieves endoplasmic reticulum stress through the PPARγ pathway. Meanwhile, FABP4 deficiency can also down-regulate the inflammatory cytokines interleukin-1β (IL-1β), IL-6, and TNF-α expression to inhibit the inflammatory response [ 29 ]. In this study, the serum FABP4 level was higher in the CAD group than in the non-CAD group, indicating an increase in serum FABP4 in CAD patients; however, FABP4 was not found to be statistically significant after adjusting for confounding factors in the multivariate study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the disruption of the BBB, FABP4 is also actively involved in apoptotic signaling activation, endoplasmic reticulum stress, oxidative stress, inflammation, and mitochondrial damage, all of which are important processes in the ischemic cascade. For example, FABP4 has been demonstrated to exacerbate I/R injury in mouse kidney tissue by modulating glucose-regulated protein 78 (GRP78)/C/EBP homologous protein (CHOP)/caspase-12 signaling to induce ER stress [ 92 ], whereas in a cellular I/R model, the involvement of FABP4 in endoplasmic reticulum stress has been found to be mediated via the PPARγ [ 102 ] and PI3K/Akt [ 103 ] pathways. As an important mediator of the inflammatory response, FABP4 is known to promote inflammation via mitochondrial uncoupling protein 2 (UCP2) [ 104 , 105 ], Toll-like receptor 4 (TLR4), and nuclear factor-κB (NF-κB) signaling [ 106 , 107 ].…”
Section: The Role Of Fabps In the Ischemic Cascadementioning
confidence: 99%